Turkish glacier inventory and classification from high-resolution satellite data - R. S. Azzoni; M. A. Sarikaya; D. Fugazza (Mediterranean Geoscience Reviews, 2020)
In view of the rapid and accelerating glacier retreat observed worldwide, the creation of an updated glacier inventory is fundamental to understand the glacier changes. Here we present the Turkish glacier inventory based on recent high-resolution satellite images (Pleiades, Google Earth™ and SPOT images). Outlines are manually digitized in ArcMap software. We identified 51 glaciers covering 12.29 km2: more than 60% of the Turkish glacierized area is located on Mount Ararat where the ice cap and four small outlet glaciers cover 7.37 km2. Turkish glaciation is characterized by small glaciers or glacierets partly debris-covered: only three glaciers (Erinç, Izbırak and Ararat glaciers) are larger than 0.5 km2. To assess the evolution of glaciers, we have focused on Mount Ararat where we digitized outlines for 1990, 1994, 2000 and 2016: in 26 years considered the glacier shows a retreat of 2.99 km2, − 29% of the initial value, showing a reduction rate dramatically higher than the main glacierized mountain ranges of the world.